2018
DOI: 10.1002/jor.24156
|View full text |Cite
|
Sign up to set email alerts
|

Tendon stem progenitor cells: Understanding the biology to inform therapeutic strategies for tendon repair

Abstract: Tendon and ligament injuries are a leading cause of healthcare visits with significant impact in terms of economic cost and reduced quality of life. To date, reparative strategies remain largely restricted to conservative treatment or surgical repair. However, these therapies fail to restore native tendon structure and function; thus, the tissue may re‐rupture or degenerate with time. To improve tendon healing, one promising strategy may be harnessing the innate potential of resident tendon stem/progenitor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 112 publications
1
56
0
3
Order By: Relevance
“…Benefiting from the positive aspects, particularly the multi-differentiation capacities and immune-privilege, TSPCs potentially represent an ideal cell source for musculoskeletal tissue regenerative medicine and therapeutic targets for numerous related diseases. Although important research has shown that TSPCs might reside within the tendon fascicles, others researchers have suggested that the epitenon might be another source of TSPCs[30]; subsequent studies have confirmed this hypothesis[30-33]. Although all TSPCs generally exhibit the characteristics of tendon stem cells, they have their own unique features when isolated from different sites in the tendon.…”
Section: Tendon Stem/progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefiting from the positive aspects, particularly the multi-differentiation capacities and immune-privilege, TSPCs potentially represent an ideal cell source for musculoskeletal tissue regenerative medicine and therapeutic targets for numerous related diseases. Although important research has shown that TSPCs might reside within the tendon fascicles, others researchers have suggested that the epitenon might be another source of TSPCs[30]; subsequent studies have confirmed this hypothesis[30-33]. Although all TSPCs generally exhibit the characteristics of tendon stem cells, they have their own unique features when isolated from different sites in the tendon.…”
Section: Tendon Stem/progenitor Cellsmentioning
confidence: 99%
“…Although all TSPCs generally exhibit the characteristics of tendon stem cells, they have their own unique features when isolated from different sites in the tendon. These findings reveal the presence of more than one source of distinct TSPCs in tendon tissue, and these populations represent a seed cells source for application in different tendon injuries according to the different cellular characteristics[30,34-36].…”
Section: Tendon Stem/progenitor Cellsmentioning
confidence: 99%
“…Similarly, other studies on tendon and ligament healing have also observed the migration of cells from the epitenon into the injury site . Recent studies using murine genetic lineage tracing have identified several distinct populations of resident tendon stem/progenitor cells that are involved in tendon healing . These include cells from tendon fascicles with markers Sca‐1, CD90, CD44, Scx, and Tnmd, cells from epitendon with markers Sca‐1, Laminin, αSMA, and PDGFα, and perivascular cells from epitendon with markers αSMA, Nes, and CD133 .…”
Section: Tendon and Ligament Structure And Healingmentioning
confidence: 89%
“…Additionally, studies have shown that they possess the superior tenogenic capacity in vitro and are more adept at healing tendon injuries in vivo as comparted to other mesenchymal stem cells (MSCs) . Bhavita and Huang recently published a very thorough review on the current understanding of tendon stem/progenitor cells …”
Section: Tendon and Ligament Structure And Healingmentioning
confidence: 99%
“…This Special Issue also contains several state‐of‐the‐art reviews on stem cells in orthopedics. Dunn et al review various biomaterial and stem cell‐based strategies for skeletal muscle regeneration, while Walia and Huang review the biology of tendon stem/progenitor cells as a basis for informing new therapeutic strategies for tendon repair. With the evolving concepts of MSCs in regenerative medicine, Barry provides an update of the long‐standing application of MSCs as a therapy for osteoarthritis and Guilak et al summarize the current state of the art in genome editing for the development of “designer” stem cells as the next generation of cell‐based therapies for musculoskeletal conditions.…”
mentioning
confidence: 99%